Construction of fills - Monahan, Edward J. (John Wiley & Sons, 1994)
The compaction guide to greater profits, less hassle. Boost your bottom line with the expert, efficient soil compaction techniques and technological solutions in this fully updated Second Edition. This revision will provide the contractor, fill inspector, and geotechnical engineer with greater coverage of environmental topics.